Estudio del contenido de metales pesados en cacao (Theobroma cacao L.) y su incidencia en la calidad de acuerdo a normativas internacionales considerando su procedencia, tipos y transformación - Ruperty Parraga, Jackson Emilio (2021)
This research work aims to study the content of heavy metals in national cocoa (Theobroma cacao L.) and its impact on quality according to international regulations considering origin, types and transformation. 7 kg of each type of cocoa were selected, controlling fermentation temperatures and with removals of 24 hours, to finish a drying in the sun up to a humidity of 7%. The first trifactorial design AxBxC was applied, to evaluate the factors involved in the study of heavy metals, being the types of samples (Factor A), localities (Factor B) and types of cocoa (Factor C). In this way, the localities significantly affect the levels of heavy metals, followed by the types of cocoa, being a2b1c0, the treatment that complies with the permissible limits of heavy metals according to international regulations (<0.01 mg / Kg) and, finally, sample types that do not vary in their result. Likewise, a trifactorial AxBxC was applied to determine the factors involved in the study of bromatological properties in the production of chocolate, where; localities (Factor A); types of cocoa (Factor B) and fermentation method (Factor C); demonstrating that the treatment a1b0c1, was the best treatment in the variable’s fat, energy, protein and titratable acidity, therefore, it is a recommended treatment for the elaboration of chocolate with excellent nutritional properties. The best sensory and nutritional characteristics according to the judges' assessment were obtained in the treatments (a0b0c1, a1b0c0, a1b0c1, a1b1c1). Keywords: Metals, Cocoa, Bromatological, Fermentation and Chocolate